Fit & active : the West Point physical development program - 4 0 16; 1953- LeBoeuf, Maureen K.,;Butler, Lawrence F.; 5 (Champaign, IL : Human Kinetics, 2008)
Explains how high schools can adapt the fitness program used at West Point to motivate students to make physical activity and fitness a key part of their lives, with suggestions for exercises and activities that students will enjoy and fulfill state and national physical education standards.
Introduction to the physical development program / Maureen K. LeBoeuf and Lawrence F. Butler -- Sport education / Joseph Doty ... [et al.] -- Program assessment / Susan Tendy -- Basic movement / Jeffrey Coelho -- Swimming / John McVan and Raymond Bosse -- Self-defense / Ray Wood and Bridget Wilson -- Fitness boxing / Ray Barone -- Obstacle courses / Thomas Horne -- Focus on fitness / William Brechue ... [et al.] -- Wellness / Ralph Pim and Whitfield East -- Personal fitness / Matthew Beekley and Jason Lehmbeck -- Tennis / Karen Peck and Sandor Helfgott -- Golf / Thomas Horne -- Ice skating / Susan Tendy and Ivan Evans -- Rock climbing / Edmund Crossley and Scott Bovee -- Soccer / Paul Gannon -- Volleyball / Lynn Fielitz -- Group fitness / Susan Tendy -- Cross-country skiing / Jeffrey Coelho.
Strategies for teachers--Cover.
Includes bibliographical references and filmographies.
Professional;Professional
Keywords: 2 -- 0; United States Military Academy. -- 6; Study and teaching.;Study and teaching. -- Physical education;Physical fitness; 20; 2